A study on knowledge management practice at United Engineers (M) Berhad / Shahinaz Abdul Rahim - Abdul Rahim, Shahinaz (2002)
The objective of the study is to identify to what extend knowledge are shred among employees of United Engineers (Malaysia) Berhad and what are the existing key elements that influence knowledge sharing activities. Secondary data has been used in this study of knowledge management practice at UEM. Data was collected based on articles, journals, textbooks, research and also Intranet database maintained at UEM. The training is an important element at UEM. It ensures continues learning and knowledge sharing among the employees. UEM has spent a millions of Ringgit on training or acquiring ne knowledge and retaining this knowledge within the organization. Level of trust and co-operation are essential to ensure continuous learning at UEM.